Pu‘olo of hope - Vodovnik, Žiga (Teorija in praksa, 2025)
The convergence of multiple crises – from deepening economic inequality and deteriorating public health to climate collapse and the rise of authoritarian regimes – reveals the ever pressing need to reimagine our social, political and economic models. The dominant frameworks we continue to rely on – our concepts, ideals, metrics, institutions, and practices – are not just insufficient, but they are structurally incapable of addressing the depth, breadth, and complexity of the challenges we face. In response, the article explores care/malama as foundational principles for a necessary paradigm shift. It examines the resurgence of Kanaka Maoli, or the Native Hawaiian world, exploring its relevance and transformative potential beyond its immediate context. Finally, the article shows the need to interpret and connect distinct, yet interrelated concepts and struggles so as to foster deeper understanding of our shared challenges and collective possibilities
Keywords: care; Evropska unija; Havaji; Hawai‘i; Kanaka Maoli; malama; ne-državni prostori; non-state space; politics; politika; pu‘uhonua; skrb